2022
DOI: 10.1021/acsami.1c21417
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Metabolism-Regulated Nanoparticles to Enhance Chemoimmunotherapy by Increasing Antigen Presentation Efficiency

Abstract: Although the strategies to induce dendritic cells (DCs) maturation and promote their antigen presentation can stimulate the tumor immune response, the endogenous deficiency and immunosuppression of DCs reduce antigen utilization, which limits antigen presentation efficiency and reduces immunotherapy effectiveness. Here, we report an endogenous stimulus-responsive nanodelivery system (DOX@HFn-MSO@PGZL). On the one hand, doxorubicin (DOX) promoted antigen presentation by DCs after the immunogenic death of tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
(78 reference statements)
0
7
0
Order By: Relevance
“…46 effectiveness of immunotherapy. 47 H-ferritin nanocages loaded with doxorubicin display potent chemoimmunotherapy through triggering ICD of tumor cells and promoting the subsequent activation and maturation of DCs. 48 Evidence suggests that mitochondrial targeted oxidative stress can disrupt endoplasmic reticulum homeostasis for evoking ER stress, with subsequent induction of massive ICD.…”
Section: Doxorubicin and Epirubicinmentioning
confidence: 99%
See 1 more Smart Citation
“…46 effectiveness of immunotherapy. 47 H-ferritin nanocages loaded with doxorubicin display potent chemoimmunotherapy through triggering ICD of tumor cells and promoting the subsequent activation and maturation of DCs. 48 Evidence suggests that mitochondrial targeted oxidative stress can disrupt endoplasmic reticulum homeostasis for evoking ER stress, with subsequent induction of massive ICD.…”
Section: Doxorubicin and Epirubicinmentioning
confidence: 99%
“…Doxorubicin‐based mannose nanogels own the advantages of remarkable stability of micelles, selective release of drugs, more favorable prognosis, increased tumor permeability, longer blood circulation, etc., in which the delivered doxorubicin triggers potent antitumor immune response via facilitating ICD, and the released mannose powerfully and synergistically alleviating breast cancer through disrupting glucose metabolism in glycolytic process as well as tricarboxylic acid cycle (TCA) 46 . Though the strategies of inducing DCs to mature and facilitating antigen presentation are capable of stimulating antitumor immune responses, the endogenous defects and immunosuppression of DCs decrease antigen utilization, thus limiting the efficiency of antigen presentation and reducing the effectiveness of immunotherapy 47 . H‐ferritin nanocages loaded with doxorubicin display potent chemoimmunotherapy through triggering ICD of tumor cells and promoting the subsequent activation and maturation of DCs 48 …”
Section: Amplifying “Eat Me Signal” By Icd Inducers For Potentiating ...mentioning
confidence: 99%
“…(G) Engineered DOX@HFn-MSO@PGZL NPs for enhanced immunotherapy by regulating glutamine metabolism. Reproduced with permission from ref . Copyright 2022 American Chemical Society.…”
Section: Nanomedicines For Amino Acid Metabolism Interventionmentioning
confidence: 99%
“…123 In this regard, an enzymeresponsive nanosystem (DOX@HFn-MSO@PGZL) was developed to enhance chemoimmunotherapy by improving antigen presentation efficiency of mature DCs (Figure 6G, Table 3). 124 Due to elevated levels of MMP-2 in the TME, two different parts including doxorubicin (DOX)-loaded heavy chain ferritin cage (DOX@HFn) and L-methionine sulfoximine (MSO)-encapsulated galactose-modified zwitterionic liposomes (MSO@GZL) were released from this nanomedicine (Figure 6G). DOX@HFn selectively delivered DOX to tumor cells via specific interaction between ferritin and transferrin receptor 1, which is highly expressed on the surface of tumor cells.…”
Section: Nanomedicines For Amino Acid Metabolism Interventionmentioning
confidence: 99%
“…Previous studies have shown that intratumoral anaerobe infection may further recruit DCs, enhance the cross-presentation of TAAs through the upregulated Cx43-dependent gap junctions (GJs), and help to restore immune surveillance in the ITME . Currently, lots of nanoparticles (NPs) have been evaluated to promote the TAAs presentation from dead/dying tumor cells to DCs or recruitment of DCs. Nevertheless, due to the limited penetration of nanoparticles in solid tumors, only restricted TAAs are exposed to DCs. ,, …”
Section: Introductionmentioning
confidence: 99%